Antiviral and Immune Enhancement Effect of Platycodon grandiflorus in Viral Diseases: A Potential Broad-Spectrum Antiviral Drug - Pei Gao; Xinshan Li; Jianlei Ding; Bosen Peng; Muhammad Munir; Fei Liu; Limin Chao; Chengfei Li; Li Wang; Jinyou Ma; Gaiping Zhang (Molecules)
Background: Traditional Chinese medicine offers potential therapeutic options for viral infections. Platycodon grandiflorus (PG) is a perennial herb known for its efficacy in treating respiratory infections, including asthma, cough, and bronchitis, making it a key focus in antiviral drug research. The purpose of the study is to provide a basis for functional studies on PG and generate new insights for treating viral diseases. Methods: Research articles from 1990 to 2024 related to PG and viruses were obtained from databases, such as PubMed, Web of Science, and Science Direct, and systematically analysed. Results: PG demonstrates inhibitory effects on viruses such as severe acute respiratory syndrome coronavirus and porcine reproductive and respiratory syndrome virus by blocking various stages of viral proliferation or activating the host immune system. It also reduces inflammation through NF-κB, PI3K/AKT, MAPK, and other signalling pathways, enhancing T cell and macrophage function and increasing host immunity. PG exhibits diverse pharmacological effects with promising clinical applications for antiviral and immune modulation. Given its medicinal significance, PG holds substantial potential for further exploration and development. Conclusion: PG, due to its antiviral, anti-inflammatory, and immune-boosting properties, can be used as an antiviral drug.